2001
DOI: 10.1176/appi.ajp.158.12.2064
|View full text |Cite
|
Sign up to set email alerts
|

Defective Relationship Between Subjective Experience and Behavior in Schizophrenia

Abstract: Patients were impaired in subjectively assessing the correctness of their knowledge, and their behavior was less determined by subjective experience than that of normal subjects. The patients' intact sensitivity to incentives has implications for cognitive remediation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 6 publications
5
31
0
Order By: Relevance
“…Thus these results support the assumption that schizophrenia patients possess a diminished capacity to metamnestically assess their own cognitive processes [11] . In these previous studies [10,12] , however, the groups were not matched for memory performance.…”
Section: Introductionmentioning
confidence: 97%
“…Thus these results support the assumption that schizophrenia patients possess a diminished capacity to metamnestically assess their own cognitive processes [11] . In these previous studies [10,12] , however, the groups were not matched for memory performance.…”
Section: Introductionmentioning
confidence: 97%
“…Spontaneous control of learning seems to be impaired in patients with schizophrenia (references), but procedures based on 'monitoring-affects-control' seem promising, insofar as patients' control abilities may be enhanced in response to monitoring support at the encoding phase. At retrieval, patients' behavior has been shown to be less determined by subjective experience than that of normal subjects (Danion et al, 2001a). Research into memory-related metacognition in patients with schizophrenia provides some rather optimistic data regarding the ability of patients with schizophrenia to improve their memory efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…It has repeatedly been observed that the retrospective confidence judgments for incorrect answers expressed by patients with schizophrenia are higher than those of matched healthy participants (Danion et al, 2001a;Moritz and Woodward, 2006;Moritz et al, 2003;Moritz et al, 2005). In the meantime, the prospective metamemory judgments of patients with schizophrenia are lower than those of healthy participants (Bacon et al, 2001;Bacon et al, 2007;Souchay et al, 2006;Thuaire et al, 2012.…”
Section: Metamemory Monitoring In Patients With Schizophreniamentioning
confidence: 97%
See 2 more Smart Citations